2018
DOI: 10.1016/j.addbeh.2018.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco harm perceptions and use among sexual and gender minorities: findings from a national sample of young adults in the United States

Abstract: Identifying as a SGM and low tobacco harm perceptions were found to be positively associated with past 30-day tobacco use. There was no interaction between SGM status and harm perceptions on past 30-day tobacco use CONCLUSIONS: Findings confirm that SGM young adults continue to disproportionately use tobacco products, compared to non-SGM young adults. More research is needed to understand moderators of the relationship between SGM status and tobacco use in young adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 26 publications
3
21
1
1
Order By: Relevance
“…Participants reported perceived relative harm of the condition-specific ECIG condition with the following item: “Compared to regular-strength non-menthol cigarettes, how harmful do you think this product is?” [37] (1 = a lot less harmful, 2 = a little less harmful, 3 = about the same, 4 = a little more harmful, 5 = a lot more harmful, 6=don’t know). The perceived addiction of a condition-specific ECIG was assessed by the following item: “What do you think the likelihood of addiction is when using this product?” [37] (1 = not at all, 2 = slightly, 3 = moderately, 4 = very much, 5 = extremely, 6 = don’t know). Responses of “don’t know” were excluded from analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Participants reported perceived relative harm of the condition-specific ECIG condition with the following item: “Compared to regular-strength non-menthol cigarettes, how harmful do you think this product is?” [37] (1 = a lot less harmful, 2 = a little less harmful, 3 = about the same, 4 = a little more harmful, 5 = a lot more harmful, 6=don’t know). The perceived addiction of a condition-specific ECIG was assessed by the following item: “What do you think the likelihood of addiction is when using this product?” [37] (1 = not at all, 2 = slightly, 3 = moderately, 4 = very much, 5 = extremely, 6 = don’t know). Responses of “don’t know” were excluded from analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Data Availability Statement: All analyses were performed in the Inter-university Consortium for Political and Social Research's Virtual Data Enclave (VDE) using the PATH Restricted Use Files [55]. Details on how to access these data are found here: https://www.icpsr.umich.edu/web/NAHDAP/ studies/36231, accessed 15 January-15 March 2021.…”
Section: Informed Consent Statement: Not Applicablementioning
confidence: 99%
“…Understanding how racial and ethnic minoritized groups and LGBTQ+ people perceive LNC cigarettes and ANDS is important for assessing how the nicotine-focused framework may benefit all populations, including whether the proposed framework may exacerbate existing smoking-related health disparities. Although a few prior LNC and/or ANDS risk perception studies have reported outcomes for people identifying as Black or African American [ 31 , 32 , 55 ], to our knowledge, this topic has been understudied among people identifying as American Indian or Alaskan Native, Asian, Hispanic, Native Hawaiian or Pacific Islander or more than one race. Further, data concerning risk perceptions among LGBTQ+ populations are also limited: one prior study examining risk perceptions among LGBTQ+ populations was restricted to young adults [ 55 ], while another included older people identifying as LGB but did not explicitly examine perceptions among people identifying as transgender [ 56 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, gay and bisexual men were equally receptive to tobacco marketing compared with heterosexual men 18. In addition, newer forms of tobacco products, including electronic cigarettes (e-cigarettes), flavoured cigars and smokeless tobacco, are marketed online and through social media and are increasingly popular among young adult sexual minorities 24–33. Similarly, the tobacco industry has a long history of targeted marketing of tobacco products, including menthol cigarettes at black, Hispanic and low-income communities.…”
Section: Introductionmentioning
confidence: 99%